Rub‐Resistant Antibacterial Surface Conversion Layer on Stainless Steel (Adv. Mater. Interfaces 11/2022). Issue 11 (14th April 2022) - Huang, Haiyue; Barber, Olivia Willilams; Yu, Zhilong; Park, Hun; Hu, Xiaobing; Chen, Xinqi; Chen, Chun‐Hu; Hartmann, Erica M.; Huang, Jiaxing
Abstract : Antibacterial Coating on Stainless Steel In article number 2200251, Haiyue Huang, Erica M. Hartmann, Jiaxing Huang, and co‐workers demonstrate an ultrathin, Cu‐containing, conformal, and continuous surface conversion layer that is grown on stainless steel through a one‐step solution‐based treatment. It shows strong adherence to the substrate and is robust enough to endure rubbing in simulated tests. Cu ions can be gradually released from the layer to induce antibacterial activities.